Management strategy of the government of Indonesia in handling the Covid-19 pandemic - Mukhtadi, Mukhtadi; Prayitno, Arief; El Harryy, Putra Sang Fajar (Technium Social Sciences Journal, 2021)
This study is to find out how the Indonesian government’s strategy in dealing with the Covid 19 pandemic over time since the discovery of covid 19. This research is qualitative, describes various related sources, and presents it about the management of pandemic covid 19 strategies. Since the covid 19 outbreak in Indonesia, various strategies have been carried out by the Indonesian government to protect its citizens from the pandemic covid 19 outbreak. Victims of covid 19, in Indonesia, have exceeded the threshold set by who (World Health Organisation) (Raoult 2021) is a common concern, the government is carrying out various strategies in addressing the pandemic covid 19. The purpose of this research is to let the public know the steps taken by the government and jointly responsible for overcoming the pandemic covid 19, because only with good cooperation can the Ovid 19 pandemic be overcome.